Rabies surveillance in Madagascar from 2011 to 2021: can we reach the target? - Andriamandimby, Soa Fy; Volasoa, Marie Hermelienne; Razafindraibe, Nivohanitra Perle; Ranoaritiana, Dany Bakoly; Razafindramparany, Mino Harimbola; Rafisandratantsoa, Théophile; Nomenjanahary, Lalaina Arivony; Rakotondrabe, Naltiana; Andriamananjara, Mamitiana Aimé; Guis, Hélène; Lacoste, Vincent; Dreyfus, Anou (Frontiers in Veterinary Science, 2023)
Rabies is endemic in Madagascar and a neglected disease. The aim of this study was to summarize human and animal rabies surveillance activities in Madagascar from 2011 to 2021. Samples from terrestrial mammals and humans were tested for rabies virus infection using direct fluorescent antibody, RT-PCR and virus isolation by the National Reference Laboratory (NRL) for rabies at the Institut Pasteur de Madagascar. Among 964 animal and 47 human samples tested, 66.7 and 70.2% were positive, respectively. The NRL received these suspect rabies samples from 48 of 114 districts of Madagascar. Most of them were submitted from the district of the capital city Antananarivo (26.3%) and mainly from its region Analamanga (68.9%). Animal samples were mainly from dogs (83%), cats (9.5%) and cattle (5.8%). Pigs, lemurs, goats accounted for less than 1%. During the 11 years of surveillance, 48 human skin and/or brain biopsy samples were received from 20 districts, mainly from Antananarivo and its surroundings (N = 13), Toamasina and its surroundings (N = 8) and Moramanga (N = 6). The high positivity rate for all species and the non-homogeneous spatial distribution of samples suggests substantial underreporting of rabies cases. There is a clear need to better understand the reasons for underreporting and prioritize rabies surveillance, prevention and control in Madagascar, with improvements in budget, education and infrastructure. A joint animal and human health rabies control program including vaccination of at least 70% of the dog population, is needed to achieve the goal of eliminating dog-transmitted human rabies by 2030 from Madagascar.